Evaluating the Potential of Container-Based Sanitation : Clean Team in Kumasi, Ghana - World Bank (World Bank, Washington, DC, 2019)
This study is focused on Clean Team, a social enterprise providing container-based sanitation (CBS) services in Kumasi, the second-largest city in Ghana with a population of 2.7 million in 2018. Clean Team is owned by Water & Sanitation for the Urban Poor (WSUP), a nonprofit partnership between the private sector, civil society, and academia. Clean Team delivers a single service: rental and regular servicing of in-house portable toilets, which includes transporting feces to a centralized treatment facility but not the processing and reuse of excreta. Customers find the Clean Team toilet appealing and Clean Team services are affordable compared to other alternatives. External subsidies, provided through public and philanthropic grant funding, have been necessary for Clean Team to cover its costs. Clean Team has been working, with support from funders and external advisers, on improving the efficiency of its services and reducing costs. Going forward, Clean Team could benefit from a clearer policy environment, which would allow them to increase the scale of their operations based on a more cost-efficient business model.